Optic disc: fovea angle : the Beijing Eye Study 2011 - Jonas, Rahul A.; Jonas, Jost B. (PLOS ONE, 2015)
Purpose To determine the optic disc-fovea angle (defined as angle between the horizontal and the line between the optic disc center and the fovea) and to assess its relationships with ocular and systemic parameters. Methods The population-based cross-sectional Beijing Eye Study 2011 included 3468 individuals. A detailed ophthalmic examination was carried out. Using fundus photographs, we measured the disc-fovea angle. Results Readable fundus photographs were available for 6043 eyes of 3052 (88.0%) individuals with a mean age of 63.6±9.3 years (range: 50-91 years) and a mean axial length of 23.2±1.0 mm (range: 18.96-28.87 mm). Mean disc-fovea angle was 7.76 ± 3.63° (median: 7.65°; range: -6.3° to 28.9°). The mean inter-eye difference was 4.01 ± 2.94° (median: 3.49°; range: 0.00-22.3°). In multivariate analysis, larger disc-fovea angle was associated (regression coefficient r2: 0.08) with older age (P = 0.009; standardized regression coefficient beta: 0.05), thinner RNFL in the nasal superior sector (P<0.001; beta: -0.17), superior sector (P<0.001; beta: -0.10) and temporal superior sector (P<0.001; beta: -0.11) and thicker RNFL in the inferior sector (P<001; beta: 0.13), nasal inferior sector (P<001; beta: 0.13) and nasal sector (P = 0.007; beta: 0.06), higher prevalence of retinal vein occlusion (P = 0.02; beta: 0.04), and with larger cylindrical refractive error (P = 0.04; beta: 0.04). Conclusions The optic disc-fovea angle markedly influences the regional distribution of the RNFL thickness pattern. The disc-fovea angle may routinely be taken into account in the morphological glaucoma diagnosis and in the assessment of structure-function relationship in optic nerve diseases. Future studies may address potential associations between a larger disc-fovea angle and retinal vein occlusions and between the disc-fovea angle and the neuroretinal rim shape.